Dunkl Operators as Covariant Derivatives in a Quantum Principal Bundle - Đurđevich, M.; Sontz, S.B. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
A quantum principal bundle is constructed for every Coxeter group acting on a finite-dimensional Euclidean space E, and then a connection is also defined on this bundle. The covariant derivatives associated to this connection are the Dunkl operators, originally introduced as part of a program to generalize harmonic analysis in Euclidean spaces. This gives us a new, geometric way of viewing the Dunkl operators. In particular, we present a new proof of the commutativity of these operators among themselves as a consequence of a geometric property, namely, that the connection has curvature zero.